Antibacterial activities and toxicological study of the aqueous extract from leaves of Alchornea cordifolia (Euphorbiaceae) - Merline Namekong Djimeli; Siméon Pierre Chegaing Fodouop; Guy Sedar Singor Njateng; Charles Fokunang; Donald Sedric Tala; Fabrice Kengni; Donatien Gatsing (BMC, 2017)
Abstract Background A. cordifolia is a plant widely used in Africa to solve many health problems. In Cameroon, it is used in the treatment of urogenital infections. As a continuation of our search for pharmacologically active agents from natural sources, the antimicrobial activity of A. cordifolia leaf extracts against E. coli and the toxicity of this extract were investigated. Methods The antibacterial activity of the aqueous extract from leaves of Alchornea cordifolia was carried out in vitro on Escherichia coli, as well as in vivo on E. coli-infected rat model. Phytochemical screening was performed using standard methods. The acute toxicity was investigated in mice, while at the end of treatment of infected rats, some biochemical, hematological and histological markers of toxicity were evaluated. Results The extract exhibited a bacteriostatic activity with MIC value of 1500 μg/ml. Phytochemical screening revealed the presence of phenols, tannins, triterpens, flavonoids, alkaloids, anthraquinones, anthocyanins, saponins and coumarins in the extract. The acute toxicity study showed LD50 values of 8.6 g/kg and 3.8 g/kg in male and female mice respectively. In vivo, the oral administration of the extract showed a dose-dependent decrease of the bacterial load as the extract at 232, 112 and 58 g/kg were able to eradicate the infection after 9, 11 and 13 days of treatment. The infected rats showed a significant (p < 0.05) increase in the level of serum creatinine, ALAT, white blood cells, and a significant (p < 0.05) decrease in the level of food and water intake, the relative weight of lungs, heart and spleen. In the treated rats, a significant (p < 0.05) increase in food and water intake and ALAT was observed at the doses of 116 and 232 mg/kg. A decrease in the red blood cells count and serum protein levels was also observed. These observations corroborate liver damages as revealed by the histopathological examination of the cross sections of this organ. Conclusion The results of this assay thus showed that the extract of A. cordifolia is bacteriostatic, therapeutic at 58 g/kg bw and may be considered as slightly and almost non-toxic on females and males mice respectively.